Longitudinal Evaluation of the Relationship Between Low Socioeconomic Status and Incidence of Chronic Obstructive Pulmonary Disease: Korean Genome and Epidemiology Study (KoGES) - Kim, Chi Young; Kim, Beong Ki; Kim, Yu Jin; Lee, Seung Heon; Kim, Young Sam; Kim, Je Hyeong (International Journal of Chronic Obstructive Pulmonary Disease, 2020)
Socioeconomic status (SES) is a strong determinant in the development of various diseases. We evaluated the relationship between SES and the incidence of chronic obstructive pulmonary disease (COPD) by using a community-based cohort data. Four-year follow-up data of 6341 adults (aged ≥ 40 years), who underwent serial pulmonary function test were analyzed. Incidence of COPD in the participants was defined as the absence of airflow obstruction compatible with COPD (pre-bronchodilator forced expiratory volume in 1 second/forced vital capacity ratio of <0.7) at baseline but documentation of airflow obstruction in serial testing. SES of patients was divided into quartiles according to household income and educational level. Multivariate logistic regression analyses were performed to estimate the association between SES and COPD incidence. A total of 280 (4.4%) patients developed COPD during the follow-up. The proportion of subjects with lowest education (elementary school) and lowest household income levels (1st quartile) was significantly higher in the COPD group than in the non-COPD group (37.9% vs 29.5%, p<0.011 and 48.4% vs 30.8%, p<0.001, respectively). Logistic regression analysis revealed that education level of elementary school was independently associated with COPD incidence after adjustment for sex, age, body mass index, white blood cell count, residence area, and occupation (odds ratio 1.879, 95% confidence interval 1.124-3.141, p=0.016). In the general population, educational level of elementary school was an independent risk factor for COPD among the components comprising SES. Our results indicate that the implementation of preventive strategies for COPD in those with low educational status could be beneficial.